HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TRIMESTER III DENGAN PEMBERIAN IMUNISASI TETANUS TOKSOID DI WILAYAH KERJA PUSKESMAS KENALI BESAR KOTA JAMBI TAHUN 2021 - Gustien Siahaan; Fatih Mila Rahmah (Universitas Adiwangsa Jambi, 2021)
One of the infectious diseases that can be fatal and contribute to maternal and child mortality is maternal and neonatal tetanus. The strategy to eliminate meternal and neonatal tetanus elimination (MNTE) is to conduct a TT (tetanus toxoid) immunization coverage program for WUS and pregnant women. Given the importance of tetanus toxoid immunization for pregnant women, knowledge of mothers and about tetanus toxoid immunization is very necessary. The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women in the third trimester with the provision of tetanus toxoid immunization in the Kenali Besar Public Health Center, Jambi City in 2021. This research is a quantitative research with a cross sectional design. This research was conducted in the Kenali Besar City Health Center Working Area on 6 to 14 October 2021. The population in this study were all third trimester pregnant women who came to check their pregnancy in the Kenali Besar Public Health Center Working Area Jambi City, with a total of 1102 respondents. The sample in the study amounted to 58 respondents. The sampling technique is purposive sampling. Based on the results of the study, most of them had a good level of knowledge, namely 39 respondents (67.2%), respondents had a positive attitude about giving tetanus toxoid immunization, as many as 39 respondents (67.2%), respondents had complete tetanus toxoid immunization, namely as many as 36 respondents (62.1%). There is a relationship between the knowledge and attitudes of pregnant women in the third trimester with the provision of tetanus toxoid immunization in the Working Area of ​​the Kenali Besar Public Health Center, Jambi City. with p value=0.000 (<0.005) It is hoped that the puskesmas can provide health education about giving tetanus toxoid immunization to pregnant women in the third trimester.